Gold-catalyzed (5,5)-rearrangement - Hu, Chao; Farshadfar, Kaveh; Dietl, Martin C.; Cervantes-Reyes, Alejandro; Wang, Tao; Adak, Tapas; Rudolph, Matthias; Rominger, Frank; Li, Jun; Ariafard, Alireza; Hashmi, A. Stephen K. (ACS catalysis, 2021)
A highly efficient gold-catalyzed cycloisomerization of 1,5-diynes was developed. Various functional groups are tolerated under the mild reaction conditions, which provides an alternative approach for the synthesis of indeno[1,2-c]furans. On the basis of mechanistic studies, including crossover experiments, deuterium labeling, and computational chemistry, the product formation proceeds via a formal [5,5]-sigmatropic rearrangement, a yet unknown reactivity pattern in gold catalysis. Instead of a synchronous concerted [5,5]-sigmatropic rearrangement and beyond an asynchronous concerted mode, each involving a single transition state, two energetically low transition states (1.8 and 5.6 kJ/mol) and an intermediate associate of the migrating benzyl cation and the vinyl gold species could be located in the computations.
Published online 19 May 2021
Published in issue 4 June 2021
Gesehen am 02.08.2021